Developing Cash Waqf Model for Micro, Small and Medium Enterprises (MSMEs) in Indonesia - Mohammad Mahbubi Ali; Shabana M. Hasan; Muhyidin (Gudang Jurnal Multidisiplin Ilmu, 2025)
MSMEs have played considerable role in the socio-economic development in Indonesia. However, the institutions continue to experience numerous challenges and constrains in various aspects. Among the prominent issues include the financing structure, lack of qualified human resources, complexity of government regulations and bureaucracy in some areas such as business start-up and etc. There is hardly any literature that has critically surveyed the issue of why the MSMEs shy away and whether there is an alternative financing model that they can adopt. The present study critically assesses the related literatures and proposes a viable cash waqf-based model which has the potential to benefit Islamic MSMEs. To ensure the successful running of the cash-waqf based model, it is recommended for the model to be established under the umbrella of a respectable Islamic body, namely Indonesia Waqf Council/Badan Wakaf Indonesia (BWI).